Travel Patterns of Marine Culinary Tourism Attractions Based on Tourist Tipology (Study Case: Muara Angke Fisheries Area) - Mujahidah, Shofa; Turgarini, Dewi; Pratama, Armandha Redo (Tourism and Hospitality Essentials Journal, 2020)
This study analyzes the potential for marine culinary tourism attraction activities in the Muara Angke Fisheries Area to be used as a marine culinary tourism attraction travel pattern based on the results of tourist typology with indicators of the development of tourist travel patterns through the availability of visiting time and tourist motivation to produce a travel pattern so that it can become material information for local government, tourism and travel businesses in an effort to increase the number of tourist visits to the Muara Angke Fishery Area, North Jakarta. The research method used is descriptive research method with a qualitative approach, by collecting data in the form of interviews, observation, and distributing questionnaires. The results of this study are identifying the potential of marine culinary tourism attraction activities in the Muara Angke Fishery Area, analyzing the typology of tourists visiting the Muara Angke Fishery Area and the travel patterns of marine culinary tourism attraction activities in Muara Angke based on the typology of visiting tourists so that the attraction activities Muara Angke culinary tourism has the potential to become a coastal culinary tourism area in DKI Jakarta.